Medicinal plants : phytochemistry, pharmacology, and therapeutics - Gupta, V. K.; Singh, G. D.; Surjeet Singh; Kaul, A. (Delhi : Daya Pub. House, 2010)
Contributed articles.
Keywords: Materia medica, Vegetable